2017
DOI: 10.1155/2017/7804763
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Potential Biomarkers of Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common supraventricular arrhythmia in the population. MicroRNAs (small endogenous noncoding RNAs) are attractive candidates as biomarkers for AF, especially considering that miRNAs are stable and are detected within easily accessible biofluids such as blood. In this review, we selected twelve studies (2012 to 2016) that were classified according to the sample type. We aimed to provide an overview of the role of circulating miRNAs in AF and to discuss the variability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…A study performed by our research group observed that the variability of miRNA could be related to the different types of samples (e.g., plasma, serum, platelet, and whole blood) and the methods of analysis used in studies. 11 Other studies have already demonstrated that the expression of the same miRNA, miR-21, may be different in plasma and the atrial tissue of patients with AF. 12 While we did not evaluate miRNA expression in atrial tissues in the present study, we observed reduced miR-21 expression in patients with persistent AF, which was consistent with previous study results.…”
Section: Discussionmentioning
confidence: 98%
“…A study performed by our research group observed that the variability of miRNA could be related to the different types of samples (e.g., plasma, serum, platelet, and whole blood) and the methods of analysis used in studies. 11 Other studies have already demonstrated that the expression of the same miRNA, miR-21, may be different in plasma and the atrial tissue of patients with AF. 12 While we did not evaluate miRNA expression in atrial tissues in the present study, we observed reduced miR-21 expression in patients with persistent AF, which was consistent with previous study results.…”
Section: Discussionmentioning
confidence: 98%
“…Besides the role as putative therapeutic targets, the cardiac-enriched nc-RNAs discussed in the present review may be employed as prognostic and diagnostic biomarkers in AF. Indeed, it is increasingly recognized that circulating plasma miRNAs could be promising biomarkers for risk stratification in AF patients [12,104]. In particular, plasma levels of two PITX2-associated miR partners, miR-1 and miR-21, are decreased in patients with sustained atrial tachycardia [105] and paroxysmal AF [59,106], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…30 Regarding AF, some studies have reported that circulating miRNAs might play a role as a biomarker. 16 Liu et al identified that downregulation of miR-150 in plasma was significantly associated with AF. 17 The downregulation of miR-150 in patients with AF was also reported by other studies 19, 20 and still other studies have separately reported changes in the expression of miR-21, miR-29, and miR-328 in AF patients.…”
Section: Main Findingsmentioning
confidence: 99%